THE PALEOGENE OF THE UTKHOLOK PENINSULA, WESTERN KAMCHATKA - Fot'yanova L.I.; Serova M.Ya.; Maslova N.P.; Levin F.D. (My University, 1996)
The paper deals with the foraminifer and fossil plant biostratigraphy of heterotopic (marine, continental, volcanogenic) Paleogene sequences of the Utkholok Peninsula situated in the Tigil' stratotype region of Western Kamchatka. The Zubchatyi Mys Formation was found to comprise heterochronous (Maastrichtian, upper Eocene) deposits. The discordant (with a hiatus), interrelationship between volcanics and the overlying continental sequence is shown. Paleontological data also suggest hiatuses between the Cretaceous and Paleogene (Ovra Cape, Uvuch Mount) and in the late Paleocene-middle Eocene interval (Uvuch Mount). The invalidity of the Uleven Group is shown, as, according to paleobotanic data, its lower part (the Zubchatyi Mys Formation) is younger (the late Eocene) than the upper Sosopkhan Formation (the early Paleocene). The "Danian" plant assemblage from the Zubchatyi Mys Formation stratotype is incompatible with the standard scheme of Western Kamchatka due to its late Eocene age.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген